Analisis Pengelolaan Keuangan Usaha Mikro Kecil Dan Menengah Pada Masa Pandemi Covid-19 - Lasri Supriana; Embun Suryani; Alamsyah Alamsyah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This study aims to analyze the financial management of MSMEs during the Covid-19 pandemic, viewed from the aspects of planning, recording, reporting, and business control. The subjects of this research are micro, small and medium enterprises (MSMEs) of Lombok Traditional Woven Fabrics located in Sukarara Village, Jonggat District, Central Lombok Regency, NTB Province. This research was conducted using a quantitative descriptive method. The conclusion in this study is to reveal the differences in the financial management of micro, small and medium enterprises (MSMEs) of Lombok Traditional Woven Fabrics in Sukarara Village, Jonggat District, Central Lombok Regency, NTB Province before the Covid-19 pandemic and and after the Covid-19 pandemic. From the results of the research that has been carried out, it can be explained that the differences in the financial management of micro, small and medium enterprises (MSMEs) of Lombok Traditional Woven Fabrics with indicators of planning, recording, reporting, and controlling are not significant.